Characterization of Cesarean Pregnant Women with a History of Previous Cesarean Section in a Tertiary Level Hospital in Lima, Peru - Fernandez Gaitan, Milagros (2024)
Objective. To describe the psychological, social and gynecological characteristics of patients with gestational lossseen at the Instituto Nacional Materno Perinatal (2022). Materials and Methods. This research corresponds to aretrospective descriptive observational study, in which 176 clinical histories of patients with gestational losses duringthe year 2022 attended by the psychology service who met the inclusion and exclusion criteria were collected. Ananalysis of frequencies and percentages of the different variables was performed in order to meet the research objectives. Results. The average age of the patients was 30 years (min: 18 years and max: 46 years), with a mean of 2.64gestations in the sample, a minimum of 0 and a maximum of 4 gestational losses. Fetal death (65.34%) was the mostfrequent diagnosis of fetal death. All the patients presented a psychological disorder, with Brief Depressive Reactionbeing the most frequent (61.36%). Seventy-eight percent came from dysfunctional families and 68.75% of the patientscame from a nuclear family. 94.89% reported not having planned the pregnancy; however, 97% indicated that theyaccepted it after learning of the pregnancy. Eighty-nine percent received support from the couple, 79.55% of whommentioned having a stable relationship; however, 51% did not receive support from the family of origin. Conclusion.Brief depressive reaction was the most frequent psychological characteristic in the patients; non-planning, partnersupport and pregnancy acceptance were the most prevalent social characteristics, and fetal death was the usualreason for fetal decease in this sample.